Introduction of medical products into healthcare practice and costs reimbursement: European experience - V. V. Omelyanovsky; S. S. Otstavnov; N. Z. Musina; V. S. Dombrovskii (Фармакоэкономика, 2018)
in the present article, we review the ways of introducing medical products into healthcare practice in countries of the european Union and compare them with the Russian experience. in this analysis, we underscore the existing differences but also identify the common aspects, for example, the mandatory stage of integrated assessment; all those are described in detail in the review. The eU experience should be considered when introducing medical products into the healthcare practice in the Russian Federation. The comprehensive assessment of new technologies will provide for the transparency of the proposed system.